Lessons Learned for Pathogenesis, Immunology, and Disease of Erythrocytic Parasites: Plasmodium and Babesia - Djokic, Vitomir; Rocha, Sandra C.; Parveen, Nikhat (Frontiers in Cellular and Infection Microbiology, 2021)
Malaria caused by Plasmodium species and transmitted by Anopheles mosquitoes affects large human populations, while Ixodes ticks transmit Babesia species and cause babesiosis. Babesiosis in animals has been known as an economic drain, and human disease has also emerged as a serious healthcare problem in the last 20–30 years. There is limited literature available regarding pathogenesis, immunity, and disease caused by Babesia spp. with their genomes sequenced only in the last decade. Therefore, using previous studies on Plasmodium as the foundation, we have compared similarities and differences in the pathogenesis of Babesia and host immune responses. Sexual life cycles of these two hemoparasites in their respective vectors are quite similar. An adult Anopheles female can take blood meal several times in its life such that it can both acquire and transmit Plasmodia to hosts. Since each tick stage takes blood meal only once, transstadial horizontal transmission from larva to nymph or nymph to adult is essential for the release of Babesia into the host. The initiation of the asexual cycle of these parasites is different because Plasmodium sporozoites need to infect hepatocytes before egressed merozoites can infect erythrocytes, while Babesia sporozoites are known to enter the erythrocytic cycle directly. Plasmodium metabolism, as determined by its two- to threefold larger genome than different Babesia, is more complex. Plasmodium replication occurs in parasitophorous vacuole (PV) within the host cells, and a relatively large number of merozoites are released from each infected RBC after schizogony. The Babesia erythrocytic cycle lacks both PV and schizogony. Cytoadherence that allows the sequestration of Plasmodia, primarily P. falciparum in different organs facilitated by prominent adhesins, has not been documented for Babesia yet. Inflammatory immune responses contribute to the severity of malaria and babesiosis. Antibodies appear to play only a minor role in the resolution of these diseases; however, cellular and innate immunity are critical for the clearance of both pathogens. Inflammatory immune responses affect the severity of both diseases. Macrophages facilitate the resolution of both infections and also offer cross-protection against related protozoa. Although the immunosuppression of adaptive immune responses by these parasites does not seem to affect their own clearance, it significantly exacerbates diseases caused by coinfecting bacteria during coinfections.